2015
DOI: 10.1007/s00253-015-7095-y
|View full text |Cite
|
Sign up to set email alerts
|

Global metabolomic responses of Nitrosomonas europaea 19718 to cold stress and altered ammonia feeding patterns

Abstract: The model ammonia-oxidizing bacterium Nitrosomonas europaea represents one of the environmentally and biotechnologically significant microorganisms. Genome-based studies over the last decade have led to many intriguing discoveries about its cellular biochemistry and physiology. However, knowledge regarding the regulation of overall metabolic routes in response to various environmental stresses is limited due to a lack of comprehensive, time-resolved metabolomic analyses. In this study, gas chromatography-mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The metabolomics can generate the metabolic profiles of living systems at a specified time and specific environmental conditions. Recently, microbial metabolomics has received much attention due to its potential applications in a wide range of research areas, and several studies have shown metabolite changes when microorganisms were exposed to limited nutrient (Jozefczuk and Al, 2010; Lu et al, 2016), heat (Jozefczuk and Al, 2010), cold (Jozefczuk and Al, 2010; Alreshidi et al, 2015), bacteriostatic agent (Mousavi et al, 2016), toxic (Planchon et al, 2017), and oxidative stress (Jozefczuk and Al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolomics can generate the metabolic profiles of living systems at a specified time and specific environmental conditions. Recently, microbial metabolomics has received much attention due to its potential applications in a wide range of research areas, and several studies have shown metabolite changes when microorganisms were exposed to limited nutrient (Jozefczuk and Al, 2010; Lu et al, 2016), heat (Jozefczuk and Al, 2010), cold (Jozefczuk and Al, 2010; Alreshidi et al, 2015), bacteriostatic agent (Mousavi et al, 2016), toxic (Planchon et al, 2017), and oxidative stress (Jozefczuk and Al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ten millilitre of P. plecoglossicida cultures incubated in five shake flasks at 12°C and 18°C, and six shake flasks at 28°C each were centrifuged at 4°C (7,000 g ) for 3 min, washed with 1 × PBS for one time, quenched in 70% (v/v) methanol, and then stored at −80°C immediately (Bolten, Kiefer, Letisse, Portais, & Wittmann, ). The quenched cells of P. plecoglossicida were transferred to new tubes, lysed by ultrasound for 5 × 3 min on ice and then extracted at room temperature with 1 ml water, 1 ml isopropanol/acetonitrile/water (3:3:2, v/v) and 1 ml chloroform in sequence (Lu, Ulanov, Nobu, & Liu, ). Individual extractions were carried out by centrifugation for 5 min at 4°C (15,000 g), and the supernatants were collected and evaporated under vacuum at −60°C.…”
Section: Methodsmentioning
confidence: 99%
“…The spectra of all chromatogram peaks were evaluated using the AMDIS 2.71 (NIST, MD, USA) program. Metabolite concentrations were reported as concentrations relative to the internal standard per gram cell dry weight (Lu et al, ). The level of certainty in our metabolite identifications should be Level 2, according to the four levels described by the Metabolomics Standards Initiative (Sumner et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Data from various studies with model denitrifiers (Giannopoulos et al, ; Olaya‐Abril et al, ; Gaimster et al, ; Gaimster et al, ; Kohlmann et al, ; Thorgersen et al, ) and nitrifiers (Qin et al, ; Cho et al, ; Wei et al, ; Mellbye et al, ; Pérez et al, ; Lu et al, ; Carini et al, ) is available for integration into models. However, soil and aquatic environments host complex microbial communities that could differ substantially in terms of the regulation and activity with respect to their nitrogen‐cycling pathways (Lycus et al, ).…”
Section: Current and Future Methods For Assessing Sources And Sinks Omentioning
confidence: 99%